PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS YOUTUBE UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Ana Robiatul Zanah; Desy Lusiyana; Jajang Rahmatudin (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to develop Youtube-based audio-visual learning media to improve students' mathematical concept understanding skills. Learning during the Covid-19 pandemic requires students to study online, resulting in a low ability to understand students' concepts, therefore alternative learning is needed. Youtube-based audio-visual learning media is an alternative learning that will facilitate students in online learning activities. The researcher uses the Research and Development (R&D) method with the ADDIE development model. The trial subjects in this development research were expert subjects, namely material experts and media experts, and the subjects of class VIII-B students of SMPN 3 Sindangwangi Satap. Determination of the subject using purposive sampling technique and data collection techniques using a questionnaire. The results showed that material expert validation got a 100% score percentage and media expert validation got a 90% score percentage so that it was included in the "Very Appropriate" or "Easy to use without revision" assessment criteria. The results of student responses get a percentage value of 93% so that it is included in the "Very Good" assessment criteria. So, this Youtube-based audio-visual learning media is suitable for students to use.